The letter and the cosmos : how the alphabet has shaped the Western view of the world - De Looze, Laurence (University of Toronto Press, 2016)
"From our first ABCs to the Book of Revelation's statement that Jesus is "the Alpha and Omega," we see the world through our letters. More than just a way of writing, the alphabet is a powerful concept that has shaped Western civilization and our daily lives. In The Letter and the Cosmos, Laurence de Looze probes that influence, showing how the alphabet has served as a lens through which we conceptualize the world and how the world, and sometimes the whole cosmos, has been perceived as a kind of alphabet itself. Beginning with the ancient Greeks, he traces the use of alphabetic letters and their significance from Plato to postmodernism, offering a fascinating tour through Western history. A sharp and entertaining examination of how languages, letterforms, orthography, and writing tools have reflected our hidden obsession with the alphabet, The Letter and the Cosmos is illustrated with copious examples of the visual and linguistic phenomena which de Looze describes. Read it, and you'll never look at the alphabet the same way again."--